Geochemical, Mineralogical and Biological study of Holocene deposits in Almuthana province, southern Iraq - Al-Khafaji, Sattar Jabar; Mahdi, Maher Mandeel (Iraqi Journal of Science, 2019)
Fifteen samples were collected from recent sediments grouping at 80 km east Samawa City, southern Iraq. Three selected samples for grain size analysis and twelve samples for chemical and biofacies analysis. Grain size analysis indicated that the sediment is mainly composed of the silt and clay with a small amount of sand. Most of the samples considered to be as clayey silt. The dominated non clay minerals are Quartz, Calcite, and Dolomite, while the clay minerals are composed of mixed Montmorillonite- Chlorite, Palygorskite, Illite and Kaolinite. Chemical analysis showed that all samples have high concentrations of SiO2 and CaO in comparison with Al2O3, MgO, Fe2O3, K2O and N2O. The identified faunas consist of a number of groups such as Mollusca, Ostracoda and Charophyta, all diagnosed genera indicated of fresh water environments. The results from all collected data are indicated that the sediments belong to flood plain deposits which deposited in fluviatile environments.